The Rhetoric of Paintings: Towards a History of Balinese Ideas, Imaginings and Emotions in the Late Nineteenth and Early Twentieth Centuries - Worsley, Peter (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
Western historical scholarship has taught us much about Southeast Asia in the period between 1800 and 1940. This was a time when the insistent, intensifying and transforming influence of Dutch colonial society and its culture became widespread in Bali and more broadly in the archipelago. Much too has been written about the analytical framework of European histories of these times. In this essay I discuss Balinese paintings from this same period which shed light on how painters and their works spoke to their viewers both about how the Balinese knew, imagined, thought and felt about the world in which they lived and about the visual representation and communication of these ideas, imaginings and feelings through the medium of narrative paintings. In this paper I hope to draw attention to a number of historiographical issues concerning the reception of the ideas, imaginings and feelings conveyed in paintings. In particular I shall have some remarks to make about the role of philology in this regard.